22. THE ROLE OF THE IDEA OF INTERETHNIC HARMONY IN ENSURING SOCIAL STABILITY - Салимов Бахриддин Лутфуллаевич. Эркинбоев Азаматжон Сайдвали ўғли (Innovative technologies in construction Scientific Journal, 2023)
In the article, it is analyzed that the issue of inter-ethnic relations is of urgent importance for all the countries of the world where we live today, because the correct establishment of inter-ethnic relations ensures the great future of the country, and in this sense, this issue is always in the center of attention in our independent Uzbekistan.